Handbook of Chinese Criminology. - Cao, Liqun (Routledge international handbooks., 2013)
As the world's second largest economy, China has made great progress in developing criminology. The Routledge Handbook of Chinese Criminology aims to be a key reference point to summarize the large body of literature in both Chinese and English about various aspects of crime and its control in China for international scholars with an interest in the development of criminological research on and in the Greater China region, and for everyone with a broad interest in international criminology. The editors of the handbook have selected authoritative contributors recognize.